Skin Sceneries of Thyroid Disorders and Impact of Thyroid on Different Skin Diseases: A Scoping Review Focused on Pediatric Patients - Ignazio Cammisa; Margherita Zona; Cristina Guerriero; Clelia Cipolla; Donato Rigante (Children)
Thyroid function plays a seminal role in the growth and development of children, and alterations in signaling pathways which interfere with the biosynthesis, transport, and metabolism of thyroid hormones might impact on the skin of such patients: this review explores the relationship between different thyroid disorders and dermatological manifestations with a particular focus on the pediatric population. Common cutaneous conditions associated with thyroid dysfunction may include chronic urticaria, vitiligo, and alopecia, which can be early harbingers of an underlying endocrine disruption. This review also highlights the growing cognizance of a “thyroid–skin axis”, with thyroid hormones influencing many physiologic processes within the skin such as keratinocyte proliferation, hair growth, and epidermal differentiation. A precocious recognition of abnormal dermatological signs can be crucial in pediatric patients for a timely diagnosis before any development of complications and for personalized treatments of an underlying thyroid disorder, which can even be symptomless at an initial phase. Despite the lack of standardized guidelines for managing dermatologic manifestations occurring in thyroid diseases, a regular screening to identify endocrine dysfunction is recommended in those children who present chronic urticaria, vitiligo, or alopecia, though further research is needed to decipher mechanisms involved in the thyroid-skin partnership and develop more targeted management approaches.